X Ray in Minor Orthopedic Injuries: Is A Must or There Is Something Else to Trust - Hesham Ben Masaud (AlQalam Journal of Medical and Applied Sciences, 2020)
Background and objectives. The management of minor orthopedic injuries is a routine work at accident & emergency departments, and although many patients undergo radiography. This study aimed to find the best screening test for a fracture in all minor orthopedic injuries with different anatomical sites. Methods. The study is a cross-sectional study. The sample was collected randomly from causality room of accident and emergency department from April to September 2006 in Abo Saleem trauma hospital; Sample size was 1000 minor orthopedic injuries with variable sex and limited age from 5-55-year ages. The data was plotted in two software programs SSPS version 10 and MEDCALC version 11.3.3.0. Results. Our study found that bone tenderness alone is the most superior screening test for requesting radiographs with any patient had the minor orthopedic injury at knee, ankle, hand, forearm, and foot. Moreover, restriction of movement alone is the most superior screening test for requesting radiographs with any patient had the minor orthopedic injury at wrist and elbow. Conclusion. “Blunt trauma or a fall as a mechanism of injury plus either of the following: if there is bone tenderness at knee, ankle, foot, hand, and forearm, or there is a restriction of movement at elbow and wrist”. This suggested decision rule for Radiography in all minor orthopedic injuries will reduce (28%) of radiographic requests from all minor orthopedic injuries without missing significant fracture.